Dynamical modelling of globular clusters: challenges for the robust determination of IMBH candidates. Issue 4 (19th September 2020) - Aros, Francisco I; Sippel, Anna C; Mastrobuono-Battisti, Alessandra; Askar, Abbas; Bianchini, Paolo; van de Ven, Glenn
ABSTRACT: The presence or absence of intermediate-mass black holes (IMBHs) at the centre of Milky Way globular clusters (GCs) is still an open question. This is due to either observational restrictions or limitations in the dynamical modelling method; in this work, we explore the latter. Using a sample of high-end Monte Carlo simulations of GCs, with and without a central IMBH, we study the limitations of spherically symmetric Jeans models assuming constant velocity anisotropy and mass-to-light ratio. This dynamical method is one of the most widely used modelling approaches to identify a central IMBH in observations. With these models, we are able to robustly identify and recover the mass of the central IMBH in our simulation with a high-mass IMBH (M_IMBH/M_GC4 per cent ). Simultaneously, we show that it is challenging to confirm the existence of a low-mass IMBH (M_IMBH/M_GC0.3 per cent ), as both solutions with and without an IMBH are possible within our adopted error bars. For simulations without an IMBH, we do not find any certain false detection of an IMBH. However, we obtain upper limits that still allow for the presence of a central IMBH. We conclude that while our modelling approach is reliable for the high-mass IMBH and does not seem to lead towards a false detection of a central IMBH, it lacks the sensitivity to robustly identify a low-mass IMBH and to definitely rule out the presence of an IMBH when it is not there.